Mechanisms of Action and Therapeutic Application of Glucagon-like Peptide-1 - Drucker, Daniel J. (Cell metabolism, 2018)
Glucagon-like peptide-1 (GLP-1) released from gut enteroendocrine cells controls meal-related glycemic excursions through augmentation of insulin and inhibition of glucagon secretion. GLP-1 also inhibits gastric emptying and food intake, actions maximizing nutrient absorption while limiting weight gain. Here I review the circuits engaged by endogenous versus pharmacological GLP-1 action, highlighting key GLP-1 receptor (GLP-1R)-positive cell types and pathways transducing metabolic and non-glycemic GLP-1 signals. The role(s) of GLP-1 in the benefits and side effects associated with bariatric surgery are discussed and actions of GLP-1 controlling islet function, appetite, inflammation, and cardiovascular pathophysiology are highlighted. Refinement of the risk-versus-benefit profile of GLP-1-based therapies for the treatment of diabetes and obesity has stimulated development of orally bioavailable agonists, allosteric modulators, and unimolecular multi-agonists, all targeting the GLP-1R. This review highlights established and emerging concepts, unanswered questions, and future challenges for development and optimization of GLP-1R agonists in the treatment of metabolic disease. Glucagon-like peptide-1 (GLP-1) has emerged as a gut-derived peptide with pleiotropic actions and has demonstrated therapeutic efficacy for cardiometabolic disorders, principally diabetes and obesity. Herein, Drucker provides an updated perspective on the physiological importance, mechanisms, and pathways underlying the efficacy and safety of native GLP-1 and GLP-1R agonists.